PERSPEKTIF DRAMATURGI ERVING GOFFMAN PADA APARAT KEPOLISIAN DALAM MENGHADAPI KASUS VIRAL - Damayanti, Febriana Firsta (Program Pascasarjana UIN Sumatera Utara, 2023)
Using the dramaturgy theory by Erving Goffman, this article tries to analyze the dramaturgy of the front stage and backstage carried out by police officers in dealing with viral cases. This research is a qualitative research with descriptive research type. The data collection technique used in this research is secondary data in the form of literature then described, processing documentation, literature study and browsing online data. From the results of the analysis, it can be seen that the police officers carry out imaging with the aim of bringing out the positive sides of themselves so as to gain public trust, but tend to cover up oblique issues regarding their institutions.Keywords: Dramaturgy, Viral Cases, Police Officer